Multi-functional properties of lactic acid bacteria strains derived from canine feces - Liu, Yunjiang; Wang, Jiali; Zheng, Haohong; Xin, Jialiang; Zhong, Zhijun; Liu, Haifeng; Fu, Hualin; Zhou, Ziyao; Qiu, Xianmeng; Peng, Guangneng (Frontiers in Veterinary Science, 2024)
Introduction: Probiotics, especially Lactic Acid Bacteria (LAB), can promote the health of host animals in a variety of ways, such as regulating intestinal flora and stimulating the host's immune system.In this study, 206 LAB strains were isolated from 48 canine fecal samples. 11 LAB strains were selected based on growth performance, acid and bile salt resistance. The 11 candidates underwent comprehensive evaluation for probiotic properties, including antipathogenic activity, adhesion, safety, antioxidant capacity, and metabolites.The results of the antipathogenic activity tests showed that 11 LAB strains exhibited strong inhibitory effect and co-aggregation ability against four target pathogens (E. coli, Staphylococcus aureus, Salmonella Braenderup, and Pseudomonas aeruginosa). The results of the adhesion test showed that the 11 LAB strains had high cell surface hydrophobicity, self-aggregation ability, biofilm-forming ability and adhesion ability to the Caco-2 cells. Among them, Lactobacillus acidophilus (L177) showed strong activity in various adhesion experiments. Safety tests showed that 11 LAB strains are sensitive to most antibiotics, with L102, L171 and L177 having the highest sensitivity rate at 85.71%, and no hemolysis occurred in all strains. Antioxidant test results showed that all strains showed good H2O2 tolerance, high scavenging capacity for 1, 1-diphenyl-2trinitrophenylhydrazine (DPPH) and hydroxyl (OH -). In addition, 11 LAB strains can produce high levels of metabolites including exopolysaccharide (EPS), γ-aminobutyric acid (GABA), and bile salt hydrolase (BSH).Discussion: This study provides a thorough characterization of canine-derived LAB strains, highlighting their multifunctional potential as probiotics. The diverse capabilities of the strains make them promising candidates for canine dietary supplements, offering a holistic approach to canine health. Further research should validate their efficacy in vivo to ensure their practical application.